A hypothesis explaining why so many pathogen virulence proteins are moonlighting proteins. Issue 5 (30th April 2018) - Franco-Serrano, Luis; Cedano, Juan; Perez-Pons, Josep Antoni; Mozo-Villarias, Angel; Piñol, Jaume; Amela, Isaac; Querol, Enrique
Abstract: Moonlighting or multitasking proteins refer to those proteins with two or more functions performed by a single polypeptide chain. Proteins that belong to key ancestral functions and metabolic pathways such as primary metabolism typically exhibit moonlighting phenomenon. We have collected 698 moonlighting proteins in MultitaskProtDB-II database. A survey shows that 25% of the proteins of the database correspond to moonlighting functions related to pathogens virulence activity. Why is the canonical function of these virulence proteins mainly from ancestral key biological functions (especially of primary metabolism)? Our hypothesis is that these proteins present a high conservation between the pathogen protein and the host counterparts. Therefore, the host immune system will not elicit protective antibodies against pathogen proteins. The fact of sharing epitopes with host proteins (known as epitope mimicry) might be the cause of autoimmune diseases. Although many pathogen proteins can be antigenic, only a few of them would elicit a protective immune response. This would also explain the lack of successful vaccines based in these conserved moonlighting proteins. Abstract : This review looks at why so many pathogen virulence proteins are from the primary metabolism and are conserved between pathogen and host.